(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article scientifically and theoretically examines the features of accounting and analysis of the financial condition of enterprises. The priorities and need for analysis are considered both at strategically important industrial enterprises and at smaller business entities in order to prevent negative consequences as a result of financial shortcomings or omissions in the enterprise. Also, by citing examples from several enterprises, several opinions have been formed on approaches to ensuring socio-economic stability by observing the rules of financial stability analysis.